Potential of Corruption in Contract Procurement of Goods and Government Services by The State Agency - I Ketut Seregig; Ni Putu Widhia Rahayu; Anita Noviyanti (Fakultas Hukum, Universitas Warmadewa, 2025)
The procurement of goods and services (hereinafter abbreviated as PBJ) by the government in Indonesia often causes problems related to law. In fact, it is not uncommon to cause company leaders to become entangled in criminal acts of corruption and other criminal acts as a result of a conspiracy carried out between businessmen and authorized officials. In this article we take a sample of one of the state-owned companies in Indonesia, namely PT.Adi Karya (Persero) Tbk, with the intention to find out the PBJ work contract management system that has so far been carried out by PT.Adi Karya (Persero) Tbk, whether it is in accordance with applicable legal provisions in Indonesia or not. The method used in extracting data in the company is the interview method. The appointment of the informant was carried out using the purposive sampling method and the qualitative writing method. After conducting a research in the company, it was found that the implementation of the contract/agreement in PBJ with other parties (government or private) in PT.Adhi Karya (Persero) Tbk is not implemented based on the Decree of the Directors of SKD Number 014-6 /2018/208 dated March 14, 2019, concerning the